Perjumpaan Adat dan Teologi HKBP dalam Konteks Bergereja di Tengah-tengah Masyarakat Batak Toba - Maurits Junard Pollatu (INSTITUTIO : JURNAL PENDIDIKAN AGAMA KRISTEN, 2018)
The Church in carrying out its mission must present the sign of Shalom to mankind. In carrying out its vocation, the church must interact with all aspects of human life, namely social economy, culture, politics and so on; so that the role of the Church can be seen and impacted on every creature in the world. HKBP is one of the Churches who made their vocation in Batak land. HKBP was greatly influenced by zending who preached the gospel to the Batak people. However, HKBP in carrying out its Theology, it is also included in cultural values, especially the culture of the Batak marriage as a form of contextual theology carried out. Therefore, HKBP can declare the sign of Shalom to the congregation through Church rules that must be followed by all members of the HKBP church. This is an effort to contextualize theology carried out by HKBP on the kinship culture of the Batak Society.Keywords: custom, theology of HKBP, Toba Batak society